2021
DOI: 10.3390/cancers13143566
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Metastatic Colorectal Cancer with Immune Oncological Therapies

Abstract: Metastatic colorectal cancer carries poor prognosis, and current therapeutic regimes convey limited improvements in survival and high rates of detrimental side effects in patients that may not stand to benefit. Immunotherapy has revolutionised cancer treatment by restoring antitumoural mechanisms. However, the efficacy in metastatic colorectal cancer, is limited. A literature search was performed using Pubmed (Medline), Web of Knowledge, and Embase. Search terms included combinations of immunotherapy and metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…These mechanisms ultimately help the tumor to escape anti-tumor immunity [ 3 , 4 , 5 , 28 , 29 , 30 , 31 ]. Therefore, monoclonal antibodies have been developed to antagonize this inhibitory signaling, and in the last decade, several randomized clinical trials have investigated the efficacy and safety of immune checkpoint inhibitors, including anti-PD-1 and anti-PD-L1 drugs [ 29 , 30 , 31 , 32 , 33 , 34 ]. The most immunological response is expected in those (metastatic) CRC patients who have tumors with deficient mismatch-repair and/or high levels of microsatellite instability [ 29 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms ultimately help the tumor to escape anti-tumor immunity [ 3 , 4 , 5 , 28 , 29 , 30 , 31 ]. Therefore, monoclonal antibodies have been developed to antagonize this inhibitory signaling, and in the last decade, several randomized clinical trials have investigated the efficacy and safety of immune checkpoint inhibitors, including anti-PD-1 and anti-PD-L1 drugs [ 29 , 30 , 31 , 32 , 33 , 34 ]. The most immunological response is expected in those (metastatic) CRC patients who have tumors with deficient mismatch-repair and/or high levels of microsatellite instability [ 29 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The KEYNOTE‐177 study revealed that for patients with dMMR/MSI‐H, pembrolizumab was superior to chemotherapy as first‐line treatment in patients with mCRC, 20 but a phase 2 study showed that there are no clear clinical benefits of pembrolizumab in patients with pMMR/MSS 21 . Combination strategies of regorafenib with immunotherapy are still under investigation 22 . In the REGONIVO study, patients receiving regorafenib plus nivolumab had a significant benefit in terms of with a median PFS (7.9 months) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…21 Combination strategies of regorafenib with immunotherapy are still under investigation. 22 In the REGONIVO study, patients receiving regorafenib plus nivolumab had a significant benefit in terms of with a median PFS (7.9 months). 23 VEGF inhibitors in combination with immune checkpoint inhibitors (ICIs) can restore tumor blood vessels to normal, increase the efficient initiation and activation of T-cell response, and reorganize the typical immunosuppressive tumor microenvironment, suggesting the synergistic effect between tumor immunotherapy and anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These are crucial factors contributing to CRC development, treatment response, and prognosis. Although significant advancement has been made in the treatment of CRC, the prognosis of patients at later stages remains poor due to tumor metastasis, chemoresistance, and other factors (Galbraith et al, 2021;Zaborowski et al, 2021). Therefore, screening patients at a high potential risk of treatment failure or poor prognosis is critical.…”
Section: Introductionmentioning
confidence: 99%